Optical Coherence Tomography Evaluation of Peripapillary and Macular Structure Changes in Pre-perimetric Glaucoma, Early Perimetric Glaucoma, and Ocular Hypertension: A Systematic Review and Meta-Analysis - Tong, Yuxin; Wang, Tiantian; Zhang, Xinyu; He, Yi; Jiang, Bing (Frontiers in Medicine, 2021)
Abstract Background: This study aimed to assess the differences in the average and sectoral peripapillary retinal nerve fiber layer (pRNFL), macular ganglion cell plus inner plexiform layer (mGCIPL), and macular ganglion cell complex (mGCC) thickness using optical coherence tomography (OCT) in patients with preperimetric glaucoma (PPG) compared to those with early perimetric glaucoma (EG) and ocular hypertension (OHT). Methods: A comprehensive literature search of the PubMed database, the Cochrane Library, and Embase was performed from inception to March 2021. The weighted mean difference (WMD) with the 95% confidence interval (CI) was pooled for continuous outcomes. Results: Twenty-three cross-sectional studies comprising 2574 eyes (1101 PPG eyes, 1233 EG eyes and 240 OHT eyes) were included in the systematic review and meta-analysis. The pooled results demonstrated that the average pRNFL (WMD = 8.22, 95% CI = 6.32 to 10.12, P < 0.00001), mGCIPL (WMD = 4.83, 95% CI =3.43 to 6.23, P < 0.00001), and mGCC (WMD = 7.19, 95% CI = 4.52 to 9.85, P < 0.00001) were significantly thinner in patients with EG than in those with PPG. The sectoral thickness of pRNFL, mGCIPL, and mGCC were also significantly lower in the EG eyes. In addition, the average pRNFL and mGCC were significantly thinner in the PPG eyes than those in the OHT eyes (pRNFL: WMD = -8.57, 95% CI = -9.88 to -7.27, P < 0.00001; mGCC: WMD = -3.23, 95% CI = -6.03 to -0.44, P = 0.02). Similarly, the sectoral pRNFL and mGCC were also significantly thinner in the PPG eyes than those in the OHT eyes. Conclusion: OCT-based measurements of peripapillary and macular structural alterations can be used to distinguish PPG from EG and OHT, which can help understand the pathophysiology of glaucoma at earlier stages. Studies that employ clock hour classification methods and longitudinal studies are needed to verify our findings.